DETERMINATION OF GLASS TRANSITION TEMPERATURE AND SURFACE PROPERTIES OF NOVEL CHALCONE MODIFIED POLY (STYRENE) BASED POLYMER - Adiguzel, Aysegul Cigdem; Cakar, Fatih; Senkal, Bahire Filiz; Cankurtaran, Ozlem; Hepuzer Gursel, Yesim; Karaman, Ferdane (VINCA INST NUCLEAR SCI, 2019)
The novel chalcone modified poly (styrene) based polymer (PVBC-DMAC) has been prepared and characterized. By using the inverse gas chromatography method, we determined glass transition temperature and surface properties of PVBC-DMAC. The obtained glass transition temperature, T-g, is a good agree with the one obtained by differential scanning calorimetry. Also considering some isomeric alcohol and acetate solvents in the temperature range from 303.2 K to 353.2 K, we investigated the polymer selectivity. The parameters K-A (acidic) and K-D (basic) of the PVBC-DMAC surface were calculated. The obtained K-A, K-D values reflected that PVBC-DMAC surface has a basic character.
Keywords: inverse gas chromatography; glass transition temperature; chalcone modified poly (styrene) based polymer; surface properties; isomer solvent seperation; INVERSE GAS-CHROMATOGRAPHY; THERMODYNAMIC INTERACTION PARAMETERS; SOLUBILITY PARAMETERS; PHOTOPOLYMER; CHEMISTRY; Thermodynamics